The role of social capital in the remittance decisions of Mexican migrants from 1969 to 2000 - Kasey Q. Maggard (Federal Reserve Bank of Atlanta, 2004)
Remittances from migrants in the United States play a major role in the Mexican economy. This paper analyzes the role that different types of social capital play in the remittances decisions of Mexican migrants. Both the decision to remit and the decision on how much to remit are analyzed. The model, based on the idea of enlightened altruism, assumes that the migrant makes his decisions based on his own well-being as well as that of his household in Mexico and his community in Mexico. Social capital is defined as the resources one gains from relationships and networks. Four different types of social capital are identified in this paper: hometown-friendship networks in the United States, family networks in the United States, other-ethnicity-based networks in the United States, and community networks in Mexico. Social capital from friendships proves to be very positively significant in both the decision to remit and how much to remit. However, for all of the observations, familial social capital is not significant in either the decision to remit or how much to remit, although familial social capital has a positive role in both tests. Other-ethnicity-based social capital negatively influences both decisions and is significant in both as well. Social capital in Mexico has a significant negative impact on the two remittance decisions. Beyond social capital, this paper provides insight into other factors that affect remittance decisions including income, bank accounts, proximity to Mexico, exchange rate, interest rate differential, community infrastructure, the number of members in the Mexican household, Mexican household consumption, and time trends. In addition, to investigate time trends further, separate regressions were run on those observations where the last migration took place before 1991 and those whose last migration occurred after 1990.
Keywords: 330; Rücküberweisungen; Social Capital; Mexiko; USA; Migranten